Determinant factors of repurchase interest of buying fashion products online in e-commerce - Nopreza, M. Andi Alwi; Sumadi (Asian Management and Business Review, 2022)
This study aims to analyze and explain the effect of e-service quality, price perception, and experiential marketing on the repurchase intention of online fashion products in e-commerce. The research uses a quantitative approach, design research with a survey to the respondents. The population is all consumers who shop for fashion through online sales in Indonesia e-commerce. Collecting data using non-probability sampling method, by means of self-selection and convenience, those who are easy to find, meet the requirements as a population and are willing to be used as research samples. The number of samples is 290 respondents. Analysis using the Structural Equation Model (SEM) method with AMOS 24.0 Software. The results of the analysis can show that e-service quality, price perception, and experiential marketing have a positive and significant effect on customer satisfaction. E-service quality, experiential marketing, and customer satisfaction have a positive and significant effect on repurchase intention. However, price perception has a negative and significant effect on repurchase intention. The novelty of this research is to explore the determinants of repurchase intention with the influencing variables consist of service quality, price perception and fashion shopping experience by Indonesian consumers in e-commerce through the intervening variable of customer satisfaction for customers in Indonesia.